STUDI FENOMENOLOGI SELF DISCLOSURE AKUN PSEUDONIM TWITTER - Hanifah Syaikhah (2021)
This study aims to know users experience self-disclosure on pseudonymous Twitter accounts and what factors encourage users to make self-disclosure on pseudonymous Twitter accounts. This research influenced by the emergence of social media Twitter phenomenon which is used by its users to disclose themselves through pseudonymous accounts. Self-disclosure by Twitter users aims to build new interactions and relationships between other users.This study conducted using qualitative approach. The type of this study was descriptive study and it used phenomenological method. The data collection techniques conducted by in-depth interviews with 7 informants. Self-disclosure occurs because of communication barriers experienced by users; such as, introverted personalities, having been victim of bullying, and more comfortable communicating through writing. The driving factor for self-disclosure of Twitter pseudonymous account users is that users are more comfortable doing self-disclosure using pseudonymous accounts because when communicating with the other person they cannot know the expression directly, users feel comfortable doing self-disclosure through pseudonymous accounts because they have one thought with the audience. and users find it more practical to disclose themselves through a Twitter account with a pseudonym. The stages of the closeness of the users start from having the same preferences, channeling emotions to get insight and support and the last is the continuation of the relationship. The self-disclosure that users make to their pseudonymous account friends determines the continuation of the relationship itself.